Specialty choices among UK medical students: certainty, confidence and key influences—a national survey (FAST Study) - Jessica Lo; Anna Collins; Sophie West; Daniel MaGee; Sara Ali; Tomas Ferreira; Anson Wong; Kavyesh Vivek; Freya F Semple; Benjamin French; Riya Patel; Guilherme Movio; et al. (BMJ Open)
Objective To explore factors influencing UK medical students’ specialty choices and examine variations in these influences across demographic groups and stages of training.Design National, cross-sectional online survey.Setting All 44 UK medical schools recognised by the General Medical Council.Participants 8,395 medical students.Primary and secondary outcomes The primary outcome was the specialty preferences of UK medical students. The secondary outcomes were factors behind these preferences and how these factors vary across demographic groups and different stages of training.Results General Practice (15.3%), Paediatrics (10.6%) and Anaesthetics (9.9%) were the most preferred specialties among final-year students. Work-life balance (84.1%), compatibility with family life (78.2%), positive training experiences (85.2%) and future specialty outlook (74.9%) were key factors influencing specialty choice. Only 23.1% of students felt confident about securing a specialty training post, with confidence higher among males (OR 1.36, 95% CI 1.21 to 1.52, p<0.0001) and privately educated students (OR 1.18, CI 1.03 to 1.35, p=0.02). Males were also more certain about their career choices (OR 1.19, 95% CI 1.07 to 1.31, p<0.0001). Confidence in securing a training place was positively associated with extracurricular achievements, including having a PubMed-indexed publication (OR 1.67, 95% CI 1.39 to 2.00, p<0.0001).Conclusions This study highlights disparities in specialty preferences and influencing factors among UK medical students. A focus on improving career guidance, exposure to various specialties and supporting equitable access to training opportunities is essential for fostering a motivated and sustainable medical workforce.